Effect of Microfibrillated Cellulose on Microstructure and Properties of Poly(vinyl alcohol) Foams - Gennaro Gentile (Polymers, 2018)
Poly(vinyl alcohol) foams, containing different amounts of microfibrillated cellulose, were prepared through an eco-friendly procedure based on high-speed mixing and freeze-drying. The effect of filler amount on cell shape and regularity was studied by scanning electron microscopy (SEM) and the evolution of the microstructure was assessed through dynamic cryo-SEM. Fourier Transformed Infrared Analysis and Differential Scanning Calorimetry measurements revealed the presence of hydrogen bond interaction among cellulosic filler and the matrix. The modulus and compression deflection of neat PVA were significantly improved by increasing the amount of microfibrillated cellulose content with respect to foams realised with pulp cellulose fibers.